2013
DOI: 10.1186/1471-2318-13-87
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of fecal incontinence among nursing home residents: a population-based cross-sectional study

Abstract: BackgroundFecal incontinence is highly prevalent among nursing home residents. Previous nursing home studies have identified co-morbidity associated with fecal incontinence, but as this population is increasingly old and frail, we wanted to see if the rate of fecal incontinence had increased and to investigate correlates of fecal incontinence further.MethodsCross-sectional study of the entire nursing home population in one Norwegian municipality. Registered nurses filled in a questionnaire for all residents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 38 publications
3
55
0
1
Order By: Relevance
“…From the results of this research, it was observed that almost 43% of the institutionalized elderly presented involuntary losses of feces, a prevalence value that agrees with the ranges presented in literature, which generally vary between 33% and 65% (Saga et al, 2013;Shah et al, 2012;Zarate et al, 2008). However, the severity of the incontinence in this sample was higher, considering that most residents with FI did not present any episodes of continence, with liquid and solid stool losses (Aslan et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…From the results of this research, it was observed that almost 43% of the institutionalized elderly presented involuntary losses of feces, a prevalence value that agrees with the ranges presented in literature, which generally vary between 33% and 65% (Saga et al, 2013;Shah et al, 2012;Zarate et al, 2008). However, the severity of the incontinence in this sample was higher, considering that most residents with FI did not present any episodes of continence, with liquid and solid stool losses (Aslan et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Both geriatric syndromes are widely studied in literature and are placed among the most important factors associated with FI, in institutionalized elderly as well as those living in community settings (AlAmeel, Andrew, & MacKnight, 2010;Aslan et al, 2009;Burge, von Gunten, & Berchtold, 2013;Melville et al, 2005;Saga et al, 2013;Shamliyan et al, 2009;Townsend et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The overall prevalence of FI in adults is estimated between 11 and 15% and increases with age, with approximately 33% of people living in retirement homes (or similar institutions) affected [1]. Stigma and social taboo are associated with FI, leading to its underreporting [2].…”
Section: Introductionmentioning
confidence: 99%